Organizational and legal basics for Federal Agency for the Commonwealth of Independent States, Compatriots Living Abroad and International Humanitarian Cooperation (Rossotrudnichestvo) - T. A. Zанко (Vestnik MGIMO-Universiteta)
The article covers the organizational and legal basics for Rossotrudnichestvo as well as its powers, objectives, activities. The author analyzes the activities of the Agency involving implementation of governmental programs in the field of international humanitarian cooperation, and highlights promising forms of work with expatriates.